2013
DOI: 10.1021/jp4084647
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Behavior of Water near Nonpolar Surfaces

Abstract: We use molecular simulation to study the wetting behavior of water near flat nonpolar surfaces. The interface potential approach is used to capture the evolution of various interfacial properties over a broad range of temperature and substrate strength. Three model substrates are considered: an atomistically detailed face-centered cubic (FCC) lattice, a graphite lattice, and a structureless wall. We first examine the evolution of the contact angle with substrate strength for conditions ranging from near drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 67 publications
10
74
0
Order By: Relevance
“…[8][9] Kumar and Errington recently provided an overview of the numerous works that have been carried out to address this question. 10 These authors concluded that "the enthalpic and the entropic contributions to the work of adhesion [...] are found to be directly related to the affinity of water for a solid surface and therefore serve as useful measures of the hydrophobicity of a surface", thus illustrating the key role of quantities such as W adh or W SL .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9] Kumar and Errington recently provided an overview of the numerous works that have been carried out to address this question. 10 These authors concluded that "the enthalpic and the entropic contributions to the work of adhesion [...] are found to be directly related to the affinity of water for a solid surface and therefore serve as useful measures of the hydrophobicity of a surface", thus illustrating the key role of quantities such as W adh or W SL .…”
Section: Introductionmentioning
confidence: 99%
“…10,[25][26] The test-area method was introduced to calculate γ LV 27 and was extended to the calculation of γ SL in Lennard-Jones systems. 28 We have introduced the phantom-wall method based on thermodynamic integration to obtain W SL .…”
Section: Introductionmentioning
confidence: 99%
“…Similar wetting behavior has also been observed in the recent Monte Carlo simulation studies performed within our group involving the Lennard-Jones fluid 2 and water. 16,17 In this work, we show how the strength of Coulombic interactions influence the temperature dependence of contact angles over a range of substrate-fluid interaction strengths.…”
Section: Introductionmentioning
confidence: 87%
“…The trends noted above for cos θ have also been reported in previous theoretical and computational studies featuring the LJ fluid 2, 13-15, 44 and water. 16,17 We now explore how the characteristics of these isotherms are related to the nature of the fluid-fluid interaction and temperature. It is noted that the value of ε wf at which the contact angle is effectively independent of temperature increases with increasing α.…”
Section: B Surface Tensionmentioning
confidence: 99%
“…[5] Two-dimensional g-C 3 N 4 , which is the most stable allotrope of carbon nitride, is of great interest to the catalytic community owing to its unique properties derived from the quantum confinement effect in the plane. [6][7][8][9][10] Due to its special physical and chemical properties, nontoxicity, excellent chemical stability and unique optical and electronic properties, it has attracted widespread attention for various applications such as materials science, environmental remediation photovoltaic solar cells, chemical sensors and photocatalysis. [11][12][13] Furthermore, g-C 3 N 4 can be easily prepared on a large scale via the hydrothermal method without any organic solvents from low-cost materials such as melamine or urea derivatives and it is insoluble in most solvents.…”
Section: Introductionmentioning
confidence: 99%